Penguatan Literasi MIPA Melalui Kegiatan Lesson Study Sebagai Upaya Menciptakan Generasi Yang Berkarakter - Almira Amir (Bioedunis Journal, 2022)
The purpose of writing this article is to explain the strengthening of scientific/MIPA literacy through lesson study activities as an effort to create a generation with character. The writing of this article uses a literature study/literature study. The required data is collected through text review, then analyzed using content analysis techniques. Based on the literature study, it shows that the effort to create a generation with character is that teachers carry out lesson study activities in a collaborative way to carry out their professional development, designing 21st century skills learning (critical thinking, creative thinking, collaborative, communicative) so that they can provide literacy strengthening, especially science/MIPA literacy